Pityriasis rosea in 12-months-old infant - Piotr Brzezinski; Ahmad Thabit Sinjab (Our Dermatology Online, 2012)
Pityriasis Rosea (PR) is a self-limiting papulo-squamous disorder characterized in its typical form by sudden onset of a larger scaly plaque (herald plaque), followed by multiple, bilateral smaller scaly lesions of oval or round shape which follow Langer's lines of cleavage on the trunk and proximal parts of extremities.Currently accepted hypothesis that the cause of this disease are human herpesvirus: HHV-6 and HHV-7.Presented case of 12-months-old infant with the image of a pityriasis rosea.PR is a common skin condition seen in children and adults. PR is rarely diagnosed in infants. It is important to distinguish it from other childhood exanthems.